Assessment of the Extent of Land Degradation in the River Loboi Watershed of Baringo County, Kenya - Bitengo, Gwako Alice; Makindi, Stanley Maingi; Moturi, Wilkister N. (My University, 2015)
Increased human population pressure and climate change constitute the global underlying root causes of accelerated and devastating land degradation processes in the Arid and Semi-Arid Lands (ASALs). River Loboi watershed, located at the lower part of the Lake Baringo Catchment, is not an exception. The area is characterized by severe vegetation degradation that has resulted in extreme soil deterioration. This study aimed to determine the extent of land degradation in the watershed with specific objectives of determining the vegetation cover and composition, observing signs of accelerated soil erosion as well as assessing the socio-economic status of the inhabitants in the watershed. Tools for data collection included structured questionnaire, observation schedules and oral histories. The measured variables were analysed using a one-way ANOVA (α =0.05) and correlation analysis. The results indicated that the whole watershed is degraded with 87.5% of the watershed being highly degraded and the remaining 12.5% moderately degraded. The overall vegetation cover was 59.6%. The middle section (Simotwe location) was the worst hit and recorded the least vegetation cover of 51.4%. In addition the watershed indicated signs of transformation towards a shrubland. The results demonstrate the urgency of developing and establishing more effective and scientific ways to curb and monitor land degradation processes in the watershed
Keywords: Land degradation; Extent; Assessment; Ground methods; Vegetation alterations; Watershed